THE ROLE OF TEACHERS IN TRANSACTIONAL AND TRANSFORMATIONAL LEARNING - Askar (Paedagogia: Jurnal Pendidikan, 2024)
The main focus of the research is to describe the main concepts of transactional learning and transformational learning. Research was carried out through literature studies, with data collection using a "thematic" or "conceptual categories" approach where the results of the study of various references were organized according to topics or issues. The results of the research show that in transactional learning, the existence of the teacher has complete authority, occupies a central position, has advantages and knows everything, while students are in a position of not knowing, and therefore learning is indoctrinative, top down, centralized, prioritizing intellectual aspects, success learning is measured on the knowledge mastered by students cognitively. Transformative learning places greater emphasis on social and cultural transformation in students, so that they have the ability and insight to face and solve problems. The existence of teachers in transformative learning is actually parallel to the existence of students. Teachers and students are learning subjects and the object is reality. Transformative learning places dialogue as the main method in learning, and therefore the existence of teachers and students learn from each other.